(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
In the present article some modem techniques, which allow qualitative and quantitative analyses in nm scale of solid surfaces with a thickness equal to some atomic layers are described. For an analysis of thin layers of surfaces classical methods are not applicable, because a very small quantity of material is used (≤ 10-13 g/cm2) and the signal coming from surface layer is covered by a large signal of the bulk. Described methods are widely applied in the study of polymers’ surfaces, specially, in analyses of biomaterial surfaces.